PERBANDINGAN ANGKA KEJADIAN PEDIKULOSIS KAPITIS ANTARA ANAK LAKI-LAKI DENGAN ANAK PEREMPUAN DI PONDOK PESANTREN AL-KAUTSAR AL-AKBAR MEDAN - Azim, Fauzan; Andrini, Nita (JURNAL IBNU SINA BIOMEDIKA, 2018)
Introduction: Pediculosis capitis is a disease in hair and scalp. This disease causes itching that can interfere with activity and reduce confidence. And can be transmitted through direct contact and indirect contact with the patient. Method: The research method used observational analysis with cross-sectional approach. Sampling was done with total sampling in pediatric population in the age group of 11-14 years with total samples 63 children, consisted 37 boys and 26 girls. Results: The study showed pediculosis capitis in boys and girls were 22 children (34.9%). The proportion of patients with pediculosis mostly occurred in girls 19 (73,1%). The analysis of the research was conducted by using chi square test. Conclusions: The results indicated that there was a significant correlation between boys and girls with pediculous capitis (pâ¤0,05). Keywords: Sex, pediculosis capitis.